Drag the tiles to the correct boxes to complete the pairs. Match each expression with its simplified form. Tiles 3a5 − (-a5) 6a7
− 2a7 -3a5 − (-2a5) 7a7 − 8a7 Pairs Simplification Monomial Expression 4a7 arrowBoth -a5 arrowBoth -a7 arrowBoth 4a5 arrowBoth
2 answers:
3a^5 - (-a^5) = 3a^5 + a^5 = 4a^5
6a^7 - 2a^7 = 4a^7
-3a^5 - (-2a^5) = -3a^5 + 2a^5 = -a^5
7a^7 - 8a^7 = -a^7
Answer: The simplified of the given expression shown below.
Step-by-step explanation:
Since, First expression, ![3a^5-(- a^5)](https://tex.z-dn.net/?f=3a%5E5-%28-%20a%5E5%29)
We can write
=
= ![4a^5](https://tex.z-dn.net/?f=4a%5E5)
Second expression, ![6a^7 - 2a^7](https://tex.z-dn.net/?f=6a%5E7%20-%202a%5E7)
⇒![6a^7 - 2a^7= 4a^7](https://tex.z-dn.net/?f=6a%5E7%20-%202a%5E7%3D%204a%5E7)
Third expression ![-3a^5 - (-2a^5)](https://tex.z-dn.net/?f=-3a%5E5%20-%20%28-2a%5E5%29)
⇒
=
= ![-a^5](https://tex.z-dn.net/?f=-a%5E5)
Fourth expression, ![7a^7 - 8a^7](https://tex.z-dn.net/?f=7a%5E7%20-%208a%5E7)
⇒ ![7a^7 - 8a^7 = -a^7](https://tex.z-dn.net/?f=7a%5E7%20-%208a%5E7%20%3D%20-a%5E7)
You might be interested in
Answer:
(7x) - 7
Hope this helps!
Hey! Your answer for this is
7x^2 + 3x^2 = 10x^2
-2x + 15x = 13x
9 - 4 = 5
Hence, 10x^2 + 13x + 5.
Hope this helps!
I need a picture to answer the question sorry
Step-by-step explanation:
3 km = 3000 m
2*3000 = $6000
Answer:
I thi k the answers is 108.36